(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
Disorders of intracardiac blood flow in patients with bronchial asthma (BA) are associated with the severity of obstructive syndrome, while changes in the lungs and minor blood circulation occur periodically as changes in blood movement. The study of disorders of the cardiovascular system in BA can play an important role in the process of their treatment.